STUDI KOMPARATIF FERTILITAS PENDUDUK ANTARA MIGRAN DAN NONMIGRAN DI PROVINSI BALI - I Ketut, Sudibia; I Nyoman, Dayuh Rimbawan; AAIN, Marhaeni; Rustariyuni, Surya Dewi (PIRAMIDA; Vol 9, No. 2 Desember 2013, 2013)
The population growth rate of the Bali Province over the period of 2000 - 2010 was 2.14 percent per year; it indicates the highest rate that was ever reached in the history of population census in Bali. Even this figure is far above the national average of 1.49 percent per year for the same period. One of the demographic components considered as the major effect on the population growth rate is the tendency of the increasing number of migrants coming to Bali. But on the other hand, it also occurred (1) an increase in the fertility rate of the population, which was indicated by an increase in TFR of Bali Province from 1.89 into 2.14 live births per woman of fertile age during the period of 2000-2010, and (2) a younger  age of the first marriage of women from 23.1 years old (in the Population Census of year 2000) into 22.4 years old (in the Population Census of  2010). Even the more surprising fact is shown by the recent findings of the Indonesian Demographic and Health Survey (IDHS) 2012 which mentions the size of the TFR of Province of Bali is 2.3 births per woman of fertile age (Central Bureau of Statistics of Bali Province, 2013).   77 In connection with the situation above, the specific objectives of this study were to (1) calculate the amount of the       rate of fertility of the migrant and non-migrant population, (2) analyze the factors that cause differences in the fertility rate of non-migrant and migrant population, (3) analyze the participation of migrant and non-migrant population in the Family Planning/ Birth Control program (KB), and (4) analyze the norms of family size of migrant and non-migrant population. To answer the above research objectives, the study was carried out in two areas, namely in Badung Regency with the highest growth rate in Bali (4.62 percent per year) and in Denpasar with a population growth rate of 4.00 percent per year. In this study, 300 respondents of fertile age couples were involved, with details of 150 respondents of migrant population and 150 respondents of non-migrant population. The sampling of respondents of migrants and non-migrants were taken by using the convenience sampling approach. An important finding in this study is (1) the average of final parity of migrants (the group of women aged 45-49 years) is 2.50 and 2.32 for those of non-migrants, (2) the higher average of final parity of migrants compared to non- migrant is determined by the younger age of first marriage, shorter duration of breastfeeding, lower participation in the family planning  program, lower educational level, as well as the lower proportion of the working women, (3) the lower use of contraception among migrants than the non-migrants, and (4) ideal number of children among the migrants range between 1-6 children, while non-migrants between 1-5 children.
Keywords: fertility, couple of fertile age, parity, family planning program